(untitled) (Al-Academy, 2026)
The concept of resistance has emerged in various intellectual and artistic practices within public spaces, aimed at raising public awareness and urging individuals to take stances against numerous humanitarian issues. Among these is the phenomenon of refugee children resulting from genocidal wars. Such humanitarian concerns have become a revolutionary preoccupation, manifesting in numerous artistic and expressive practices in various forms, to showcase the freedom of individual creativity and its collective interaction in public spaces. The giant puppet "Amal" is one such project that conveyed the suffering of refugees worldwide, particularly children who are forced by wars and conflicts to leave their homes and become separated from their families. This puppet became a symbol of struggle and a form of protest, penetrating the visual field towards areas of common public thought, turning its journey through the streets into a space for engaging the audience and confronting them directly with these pressing issues.